2011
DOI: 10.5402/2011/825073
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Heat Transfer for Heat Pipe and Its Correlation

Abstract: In spite of wide application of heat pipe in microelectronics cooling system, a complete understanding of heat pipe mechanism has not yet been completed. An experimental investigation of heat transfer performance of a heat pipe for dry condition and with three different liquids as acetone, methanol, and water having four fill ratios, for each liquid has been conducted in the present study. The heat pipe was 5 mm in diameter and 150 mm long with a thermal capacity of 10 W. The evaporator and condenser's tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…For Run 21, very high convective heat transfer coefficient (h c ¼ 6136 W/m 2 K) was observed in the condenser section, which may be due to phase change in this section. Among the previous works, Mozumder et al, 56 Imura et al, 57 Shiraishi et al, 58 Zaghdoudi et al, 59 Song et al 60 also reported convective heat transfer coefficient of the order of 10 3 in the heat pipe. The overall heat transfer coefficient (h o ) for the heat pipe was found to be lower than that of evaporator and condenser sections in both the cases…”
Section: Thermal Resistance and Heat Transfer Coefficientmentioning
confidence: 95%
“…For Run 21, very high convective heat transfer coefficient (h c ¼ 6136 W/m 2 K) was observed in the condenser section, which may be due to phase change in this section. Among the previous works, Mozumder et al, 56 Imura et al, 57 Shiraishi et al, 58 Zaghdoudi et al, 59 Song et al 60 also reported convective heat transfer coefficient of the order of 10 3 in the heat pipe. The overall heat transfer coefficient (h o ) for the heat pipe was found to be lower than that of evaporator and condenser sections in both the cases…”
Section: Thermal Resistance and Heat Transfer Coefficientmentioning
confidence: 95%
“…Along with the material and the working fluid; the dimensions, wick structure and orientation of the heat pipe also have a major effect on the heat transfer limits. Qpedia eMagazine [3] discusses the impact of orientation and wick structures on the thermal performance of a heat pipe. Grooved, mesh and sintered wicks were tested at different angles of inclination for the diameters 4 mm, 5 mm and 6 mm.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The effect of phase change of a different working fluid (acetone-methanol-water) on the characteristics heat transfer of the heat pipe became more complicated and was investigated experimentally for four filling ratios. 16 It is shown that the optimum value of the filling ratio is 85%. Also, a new correlation dependent on different parameters, such as boiling temperature, evaporator wall temperature, filling ratio, and latent heat of evaporation, was found, which coincided with experimental data.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental results showed that for different input powers, the efficiency of the TPCT increases up to 14.7% when Al 2 O 3 /water nanofluid was used instead of pure water, and the temperature distributions on TPCT also confirm these results. The effect of phase change of a different working fluid (acetone‐methanol‐water) on the characteristics heat transfer of the heat pipe became more complicated and was investigated experimentally for four filling ratios 16 . It is shown that the optimum value of the filling ratio is 85%.…”
Section: Introductionmentioning
confidence: 99%